Game Monopoli Sebagai Media Pembelajaran Mata Kuliah Kewarganegaraan - I Gede Suardika; I Gusti Made Murjana (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2017)
Motivation to learn Civics among students is still lacking. The game can be used as a medium to improve student learning motivation. Some studies suggest that the monopoly game can be used as a medium of learning. In this research, analysis, design, and implementation of instructional media courses citizenship in the form of a monopoly game. The method used to establish a medium of learning is a method of Multimedia Development Life Cycle. Based on the results of beta testing has been conducted on 30 respondents can be concluded that this game can be used as a medium of learning subjects Citizenship where the approval rate of the game is to help users in learning the material subject Citizenship by 86%, as well as the level of agreement on the explanation of material subject Citizenship in this game easily understood by 70%. Keywords: Media Education, Citizenship Course, MDLC, Game Monopoly